2016
DOI: 10.3847/0004-637x/823/1/4
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Coupled Stellar Motions in the Galactic Disk by Orbiting Satellites

Abstract: We use a set of high-resolution N-body simulations of the Galactic disk to study its interactions with the population of satellites predicted cosmologically. One simulation illustrates that multiple passages of massive satellites with different velocities through the disk generate a wobble, having the appearance of rings in face-on projections of the stellar disk. They also produce flares in the disk outer parts and gradually heat the disk through bending waves. A different numerical experiment shows that an i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 42 publications
(49 reference statements)
8
66
0
Order By: Relevance
“…The vertical asymmetries in the stellar density may be due to an ancient impact, possibly by the Sagittarius (Sgr) dwarf galaxy (Widrow et al 2012), with support for the impact hypothesis coming not only from theoretical investigations (Purcell et al 2011;Gómez et al 2012a), but also from an observed vertical wave in mean metallicity (An 2019), inferred from SDSS photometry, with features similar to the observed density wave. The novel phase-space structures noted by Antoja et al (2018) also offer support to the impact hypothesis, as such features had been predicted as a consequence (Purcell et al 2011;Gómez et al 2012b;D'Onghia et al 2016;Fux 2001). Recently, too, the discovery of stars with retrograde motion in the disk has led to determination of a previously unidentified ancient impact, from Gaia-Enceladus (or the Gaia-Sausage) in the inner halo Belokurov et al 2018).…”
Section: Introductionmentioning
confidence: 77%
“…The vertical asymmetries in the stellar density may be due to an ancient impact, possibly by the Sagittarius (Sgr) dwarf galaxy (Widrow et al 2012), with support for the impact hypothesis coming not only from theoretical investigations (Purcell et al 2011;Gómez et al 2012a), but also from an observed vertical wave in mean metallicity (An 2019), inferred from SDSS photometry, with features similar to the observed density wave. The novel phase-space structures noted by Antoja et al (2018) also offer support to the impact hypothesis, as such features had been predicted as a consequence (Purcell et al 2011;Gómez et al 2012b;D'Onghia et al 2016;Fux 2001). Recently, too, the discovery of stars with retrograde motion in the disk has led to determination of a previously unidentified ancient impact, from Gaia-Enceladus (or the Gaia-Sausage) in the inner halo Belokurov et al 2018).…”
Section: Introductionmentioning
confidence: 77%
“…Such a wave that propagates through the disk tends to form a two-armed ring-like pattern with over-dense and under-dense regions together with strong bending vertical velocities (see e.g. Gómez et al 2013;D'Onghia et al 2016).…”
Section: Interaction With a Massive Satellitementioning
confidence: 99%
“…This feature is interpreted as the incomplete phasemixing phenomenon occurring in the stellar disk and a manifestation of the disk being locally out of dynamical equilibrium. Recent studies using analytic models (Antoja et al 2018;Binney & Schönrich 2018) or numerical simulations (D'Onghia et al 2016;Laporte et al 2018a;Darling & Widrow 2019) interpreted this feature as likely caused by the coupling of vertical and in-plane motions induced by the passage of a satellite galaxy through the Galactic disk. In fact in the presence of rings induced by the impact of a satellite, the intra-ring underdense regions coincide with a local increase of the characteristic scale height (see Fig.…”
Section: Interaction With a Massive Satellitementioning
confidence: 99%
See 1 more Smart Citation
“…Purcell, et al (2011) modeled the effects produced in the Milky Way by the infall of Sgr, yielding spiral wave formation, enhanced bar evolution, and flaring at the edges of the Milky Way's disc. Gómez, et al (2012) and D'Onghia, et al (2016) also simulated the Sgr impact, producing vertical density waves and disc thickening, respectively. Widrow & Bonner (2015) used a similar large satellite to that of Quillen, et al (2009), and in addition to observing the same spirals and thickening as their predecessors, were able to show that the effects of a single perturbance are quickly damped away within the disc and repeated, cyclic perturbances are necessary to induce long-term effects.…”
Section: Introductionmentioning
confidence: 99%